Adverse selection, public information, and underpricing in IPOs - Leite, Tore (Journal of Corporate Finance, 2007)
This paper generalizes the informational environment of the Rock model to address empirical evidence and conjectures that cannot be addressed within the standard model based on informed and uninformed investors such as underpricing being positively related to market returns observed prior to the IPO, the number of IPOs being positively related to market returns, underpricing being partly predictable based on public information, and the return to uninformed participation being negative overall but positively related to market returns observed prior to the IPO. Finally, the model suggests that a positive relation between market returns and underpricing need not represent an inefficiency in the pricing of IPOs.